Growth and architecture of dwarf, semidwarf and tall oat lines under northern latitudes - Mäkelä, Pirjo; Muurinen, Susanna; Peltonen-Sainio, Pirjo (MTT, 2004)
The Finnish particularly short growing season with frequently occurring fluctuations in climate affects crop growth and yield formation and especially quality severely. Dwarfing genes have been effective sources for lodging control that have enabled higher input use, but also known to enhance floret and grain set and survival. The primary effects of the dwarfing genes on growth are demonstrated for wheat, whereas few publications concern oat. We aimed to describe pre- and post-anthesis growth of dwarf and semidwarf oat lines at high latitudes and evaluate their yielding capacity and contribution to differences in tillering, leaf characteristics and source-sink interaction in productivity. Three experiments (1999-2001) in a randomised complete block design with five replications (10 m2) were conducted at the Suitia Experimental Farm. Plant material consisted of Grane (dwarf, 73 cm), Pal (dwarf, 70 cm), Hja 76416 (semidwarf, 81 cm), Salo (semidwarf, 80 cm), Veli (tall, 104 cm), and Jalostettu maatiainen (tall, 110 cm). Plants were analysed for leaf area formation and biomass accumulation separately for main stem and tillers, measured for length (cm), and divided into head, leaf laminae, dead leaves, leaf sheaths, peduncle, nodes and the remainder of the stem. Number of plants, tillers, and heads m-2, date of heading and maturity, and lodging-% were recorded. Additional parameters were calculated. Statistical analyses were carried out with the Statistical Analysis System. Long leaf area duration and high leaf area index were associated with increased grain yield probably due to more persistent and active assimilation. Higher peduncle, straw and node weights associated with increased grain yield which may be due to more abundant assimilate reserves. Longer straw and peduncle, however, resulted in lower grain yield.
Keywords: Ka; kaura; kääpiö; korsi; lehtiala; lehtialan kesto; kasvusto; Avena sativa L.; dwarfing gene; internode; leaf area duration; plant height; plant stand